The nexus among competitively valued exchange rates, price level, and growth performance in the Turkish economy: New insight from the global value chains - Umar Aliyu Shuabiu; Mohammed A. M. Usman; Behiye Çavuşoğlu (Journal of Risk and Financial Management, 2021)
Currently, global value chains (GVCs) are increasingly shaping the global economy, covering a growing share of international trade, GDP, and employment globally. Global trade is impacted by the emergence of GVCs in areas as diverse as commodities, electronics, and business service outsourcing, among other areas, since the countries involved in the GVCs hold some value(s) and benefit(s) from the exports of the finished product. In this study, the nexus among Competitively Valued Exchange Rates, Price level, and Growth Performance in the Turkish Economy; New insight from the GVCs is investigated using annual data from 1980 to 2020 within the framework of the ARDL bound test, Bayer and Hanck Cointegration (BHC) test, and ECM. The study results revealed that the relationship among real effective exchange rate, exports, and imports induced economic performance and external trade competitiveness particularly when directed at GVCs in both the short and long run. The study recommends that policies enhancing a 10% equilibrium convergence are required annually to competitively minimize the dependence on foreign value-added inputs by importing only world-class inputs for value addition and exports benefits in the competitive GVCs world. Furthermore, monetary policy, GVCs, and economic growth should be investigated.
Keywords: F00; F04; F31; 330; Turkey; economic growth; ARDL bounds test; exchange rate; foreign trade